1991
DOI: 10.1002/cm.970200404
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization and actin binding properties of ABP‐50: The elongation factor‐1 alpha of Dictyostelium

Abstract: ABP-50 is the elongation factor-] alpha (EF-1 alpha) of Dictyostelium discoideum (Yang et al.: Nature 347:494-496, 1990). ABP-50 is also an actin filament binding and bundling protein (Demma et al.: J . Biol. Chem. 265:2286-2291. In the present study we have investigated the compartmentalization of ABP-50 in both resting and stimulated cells. Immunofluorescence microscopy shows that in addition to being colocalized with F-actin in surface extensions in unstimulated cells, ABP-50 exhibits a diffuse distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 29 publications
5
57
1
Order By: Relevance
“…In our study, we found that EF-1α immunofluorescent signal was co-localized with F-actin, which has been reported previously (24). We also demonstrated that the knockdown of EF-1α resulted in the decrease of growth in Du145 cells, which was consistent with the inhibition of migration and invasion.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we found that EF-1α immunofluorescent signal was co-localized with F-actin, which has been reported previously (24). We also demonstrated that the knockdown of EF-1α resulted in the decrease of growth in Du145 cells, which was consistent with the inhibition of migration and invasion.…”
Section: Discussionsupporting
confidence: 91%
“…Immunoprecipitates were washed and processed for SDS-PAGE and Western blotting as described in Ref. 40. Immunoprecipitates of eIF4G antibody or control monoclonal antibody, supernatants, and total lysates were immunoblotted with anti-eIF4G (top half of gel) or anti-eIF4E (bottom half of same gel) to visualize eIF4G as a 220-kDa band and eIF4E as a 25-kDa band.…”
Section: Methodsmentioning
confidence: 99%
“…; Dharmawardhane et al, 1991). The use of this antiserum for the immunoblot shown in Figure 5A indicates the identity of pp50, which eluted from both the tubulin (lane 1) and CaM (lane 2) affinity matrices.…”
mentioning
confidence: 89%